(untitled) (قضايا سياسية, 2023)
Cultural identity is the most important tributary of intellectual identity in any society, and there is no doubt that the loss of self-identity simply means the loss of a human being, and here intellectual alienation and its effects on the human being occur that push him to surrender to the other, and this needs solutions that start with factors of socialization, media, religious institutions, as well as political parties actors..